Implementasi Ekstrakurikuler Pramuka Penggalang dalam Membentuk Karakter Disiplin Siswa SD Negeri Watukelir - Azizah, Athifah Nur; Nurhidayati , Nurhidayati; Ratnaningsih, Arum (Jurnal Humaniora dan Ilmu Pendidikan, 2024)
Purpose: This study aimed to examine the implementation of Cub Scout extracurricular activities in shaping the disciplinary character of fourth- and fifth-grade students at SD Negeri 1 Watukelir. This research highlights the significance of early character education and the strategic role of scouting in cultivating discipline, responsibility, and independence among young learners. Methodology/approach: A qualitative descriptive approach was used. Data were collected through interviews with school personnel, observations of scouting activities, and documentation analysis. The data were analyzed using the stages of data collection, reduction, presentation, and conclusion drawing to ensure comprehensive and credible results. Results/findings: The findings indicate that the Cub Scout program is well-structured and is routinely implemented. Activities included regular training sessions on discipline, marching, proper use of Scout uniforms, and various outdoor exercises. These initiatives have significantly influenced students' disciplinary behavior, as reflected in improved punctuality, adherence to school rules, and greater engagement in class activities. Key supporting factors include strong commitment from Scout leaders, institutional support from schools, and enthusiastic student participation. Conclusions: The study concludes that Cub Scout extracurricular activities play a vital role in developing students’ disciplinary character when conducted consistently and aligned with their developmental needs. Limitations: The research was limited to a single school and a brief observation period, restricting insights into the long-term impacts. Contribution: This study reinforces the educational value of Scouting as a practical tool for fostering discipline among elementary school students.